Impact of information on demand for safe food - Hoffmann, Vivian; Kariuki, Sarah; Murphy, Mike; Ndisio, Boaz; Ochenje, Ibrahim; Okoth, Sheila (International Food Policy Research Institute, 2023)
Problems caused by eating unsafe food are a major health issue in many countries. Contamination by bacteria or toxins can cause these health risks, particularly for young children whose bodies are still developing. It can be difficult to know which foods are risky because you usually cannot tell by looking if food is contaminated. The goal of this research was to see whether giving consumers in Kenya information about one of these contamination risks would make them choose to purchase different products.